An overview of intelligent selection and prediction method in heterogeneous wireless networks - Salih Y.K.; See O.H.; Ibrahim R.W.; Yussof S.; Iqbal A. (Central South University of Technology, 2023)
Heterogeneous wireless access technologies will coexist in next generation wireless networks. These technologies form integrated networks, and these networks support multiple services with high quality level. Various access technologies allow users to select the best available access network to meet the requirements of each type of communication service. Being always best connected anytime and anywhere is a major concern in a heterogeneous wireless networks environment. Always best connected enables network selection mechanisms to keep mobile users always connected to the best network. We present an overview of the network selection and prediction problems and challenges. In addition, we discuss a comprehensive classification of related theoretic approaches, and also study the integration between these methods, finding the best solution of network selection and prediction problems. The optimal solution can fulfill the requirements of the next generation wireless networks. © 2014 Central South University Press and Springer-Verlag Berlin Heidelberg.